Narrativas jornalísticas como produção material da cultura:a presença do imaginário na construção ideológica em torno da realidade - Borges, Wilson Couto (2009)
The present work brings as central subject the narrative constructions of the press around the need of use of the Brazilian Armed Force and the National Force of Public Safety for the contention of the "growing criminality" in the city of Rio de Janeiro. Actually, far away from representing a simple diffusion of information, this is a political action which, subsumed within the objectivity notion, occupies a strategic place in the celebration of hegemonic social senses, especially for the historical relationship that the structure of the news maintains with the popular culture matrices. In that process, the social imaginary emerges as an instance over which one tries to take over control, which also means to say that, in the struggle for the fixation of meanings, imagination is a constituent element both of the creation of the narration as of the repository to which society appeals to produce new actions. With this aim, the research is developed around the notion of directionality of the social actors' answers starting from the social imaginary "control", then pointing to the way how certain reading protocols end up addressing the information. Insofar as a certain theme is not contemplated by the newspapers it seems not to exist. Therefore, the news organs become lords of the memory and the forgetfulness in the construction of social representations. In this regard, culture - as a group of the material representations of a society - turns into the main object of disputes, particularly for authenticating the predominantly built meanings. Hence, the antagonism between the proposals of Viva Rio and CEUEP illuminates our approach in what concerns the presence of the ideological struggle and the crystallization of a triumphant vision.